Creep properties and design curves for nitrogen enhanced grade of 316LN stainless steel. (July 2015) - Mathew, M. D.; Ganesan, V.; Ganesh Kumar, J.; Laha, K.
Abstract : 316L(N) stainless steel (SS) containing 0·02–0·03 wt-% carbon and 0·06–0·08 wt-% nitrogen is the principal material for the high temperature structural components of the prototype fast breeder reactor in India. In order to increase the economic competitiveness of sodium cooled fast reactors (SFRs), there is a strong desire to increase the design life from the current level of 40 years to at least 60 years for the future reactors. As a part of the efforts to develop materials with superior mechanical properties suitable for longer design life, the influence of nitrogen at concentrations higher than 0·07 wt-%, on the high temperature mechanical properties of type 316L(N) SS is being studied. Four heats of 316L(N) SS, containing 0·07, 0·11, 0·14 and 0·22 wt-% nitrogen have been evaluated extensively in terms of their tensile, creep, low cycle fatigue and creep fatigue interaction properties. Based on these studies, the nitrogen content has been optimised at 0·14 wt-%. This nitrogen enhanced grade of steel (NE316LN SS) was found to have significantly better tensile, creep, low cycle fatigue and creep-fatigue properties as compared to the PFBR grade of 316L(N) SS. This paper presents the influence of nitrogen on the creep deformation, damage and fracture behaviour of NE316LN SS. Design of high temperature SFR components is made on the basis of RCC-MR design code. The creep properties of NE316LN SS have been analysed in terms of the procedures for generation of the design code. Time–dependent design curves have been generated.